Chemical Constituents of the Marine-Derived Fungus Aspergillus sp. SCS-KFD66 - Chang-Liang An; Fan-Dong Kong; Qing-Yun Ma; Qing-Yi Xie; Jing-Zhe Yuan; Li-Man Zhou; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Marine Drugs, 2018)
Five new compounds named asperpenes A-C (1⁻3), 12,13-dedihydroversiol (4), and methyl 6-oxo-3,6-dihydro-2H-pyran-4-carboxylate (5), along with 10 known compounds (6⁻15), were isolated from the fermentation broth of Aspergillus sp. SCS-KFD66 associated with a bivalve mollusk, Sanguinolaria chinensis, collected from Haikou Bay, China. The structures of the compounds, including the absolute configurations of their stereogenic carbons, were unambiguously determined by spectroscopic data, single-crystal X-ray diffraction analysis, and electronic circular dichroism (ECD) spectral analysis, along with quantum ECD calculations. The growth inhibitory activity of the compounds against four pathogenic bacterial (Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Listeria monocytogenes ATCC 1911, and Bacillus subtilis ATCC 6633), their enzyme inhibitory activities against acetylcholinesterase and α-glucosidase, and their DPPH radical scavenging activity were evaluated.